Cooperativity‐Driven Reactivity of a Dinuclear Copper Dimethylglyoxime Complex. Issue 22 (20th March 2023) - Petrikat, Raphael I.; Steiger, Sophie T.; Barani, Elham; Boden, Pit J.; Huber, Maximilian E.; Ringenberg, Mark R.; Niedner‐Schatteburg, Gereon; Fink, Karin; Becker, Sabine
Abstract: In this report, we present the dinuclear copper(II) dimethylglyoxime (H2 dmg) complex [Cu2 (H2 dmg)(Hdmg)(dmg)] + (1 ), which, in contrast to its mononuclear analogue [Cu(Hdmg)2 ] (2 ), is subject to a cooperativity‐driven hydrolysis. The combined Lewis acidity of both copper centers increases the electrophilicity of the carbon atom in the bridging μ 2 ‐O−N=C‐group of H2 dmg and thus, facilitates the nucleophilic attack of H2 O. This hydrolysis yields butane‐2, 3‐dione monoxime (3 ) and NH2 OH that, depending on the solvent, is then either oxidized or reduced. In ethanol, NH2 OH is reduced to NH4 +, yielding acetaldehyde as the oxidation product. In contrast, in CH3 CN, NH2 OH is oxidized by Cu II to form N2 O and [Cu(CH3 CN)4 ] + . Herein are presented the combined synthetic, theoretical, spectroscopic and spectrometric methods that indicate and establish the reaction pathway of this solvent‐dependent reaction. Abstract : First check your solvent : In a dinuclear dimethylglyoxime copper(II) complex, hydrolysis of one ligand is facilitated by the cooperative effect of both Cu II ions. Hydrolysis yields butane‐2, 3‐dione monoxime and NH2 OH; depending on the solvent used, the latter is either oxidized to N2 O (in CH3 CN) or reduced to NH4 + (in ethanol). A combined approach of experimental, theoretical, and spectroscopic methods allowed the reaction mechanism to be suggested.